(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2022)
In this paper, a planar antenna for Long Term Evolution (LTE) bands and Wireless Local Area Network (WLAN) is proposed. The antenna is based on a coupled-fed monopole with a distributed inductor and a direct-fed monopole. These three components form two bands of operations namely a low operating band from 0.59 to 0.635 GHz and a high operating band from 1.67 to 2.80 GHz. The two operating bands satisfy the WMTS 610, UMTS 1700, GSM 1800, LTE 1900, LTE 2100, WLAN 2400, LTE 2600 and WLAN 3600 applications. The proposed antenna having dimensions 75 × 10 × 0.8 mm3 is suitable for the top edge of a mobile handset and a copper plate of 75 × 100 mm2 (5 inches screen plate), is used as the ground plane system.